European dimensions in Romanian theological discourse - Chirilă, Ioan (HTS teologiese studies, 2009)
This article underlines particularly those aspects of Romanian theology that distinguish it from other theological reflections. By making use of liturgical discourse, Romanian theology reflects the ecumenical dimension of the prayers of the Divine Liturgy. It is this specificity that provides Romanian theology’s missionary dimension within the European context. The author introduces the idea that theology is not an academic mission reserved to a group of intellectuals or to the hierarchy of the church; it is rather open to every believer – every believer is asked to be a theologian, to be a person of prayer, to speak about God while being in God. Another point of interest is the God-humanity-world relationship in an era of globalisation, with regard to which the author stresses the need for equilibrium between spiritual and scientific values and that Romanian Orthodox theology is an authentic theology of equilibrium.